2016
DOI: 10.1080/02699052.2016.1193631
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease and chronic traumatic encephalopathy: Distinct but possibly overlapping disease entities

Abstract: Background Alzheimer’s disease (AD) and chronic traumatic encephalopathy (CTE) have long been recognized as sharing some similar neuropathological features, mainly the presence of neurofibrilary tangles and hyperphosphorylated tau, but have generally been described as distinct entities. Evidence indicates that neurotrauma increases the risk of developing dementia and accelerates the progression of disease. Findings are emerging that CTE and AD may be present in the same patients. Clinical presentation We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 116 publications
(132 reference statements)
1
33
0
Order By: Relevance
“…6 We expanded upon these findings showing that TBI can contribute to tauopathy leading to CTE, Alzheimer's disease (AD), or, in rare cases, CTE/ AD. 7 Hyperphosphorylated tau aggregates around venules and begins to form oligomers and neurofibrillary tangles. We recently showed that this perivascular tau was associated with an increase in endoplasmic reticulum (ER) stress activation.…”
Section: Introductionmentioning
confidence: 99%
“…6 We expanded upon these findings showing that TBI can contribute to tauopathy leading to CTE, Alzheimer's disease (AD), or, in rare cases, CTE/ AD. 7 Hyperphosphorylated tau aggregates around venules and begins to form oligomers and neurofibrillary tangles. We recently showed that this perivascular tau was associated with an increase in endoplasmic reticulum (ER) stress activation.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of Aβ plaques after rmTBI may be greater, because not all who suffer rmTBI develop CTE. Collectively, these observations demonstrate overlap in the pathology of severe TBI, rmTBI (including CTE), and AD, and emphasize that polypathology, rather than just tauopathy or amyloidopathy, more accurately underlies the chronic neuropathological course of TBI (Turner et al, 2016; Washington et al, 2016). In this regard, evidence is emerging that other proteins, such as alpha-synuclein and TDP-43, can accumulate in the brain after TBI (Crane et al, 2016; Johnson et al, 2011; McKee et al, 2010).…”
Section: Evidence Linking Tbi and Admentioning
confidence: 77%
“…Our group and others have shown that looking earlier in the disease process may be more valuable in finding a treatment solution that can be clinically successful. Secondary injury mechanisms such as oxidative stress, endoplasmic reticulum (ER) stress, and neuroinflammation play a more important role in disease onset than previously assumed [1][2][3][4]. These secondary injury mechanisms can be primed by genetic predisposition and triggered by insults such as neurotrauma, drug abuse, and cardiovascular disease [5][6][7].…”
Section: Introductionmentioning
confidence: 90%